Class I HDAC inhibitors enhance YB‐1 acetylation and oxidative stress to block sarcoma metastasis. (31st October 2019) - El‐Naggar, Amal M; Somasekharan, Syam Prakash; Wang, Yemin; Cheng, Hongwei; Negri, Gian Luca; Pan, Melvin; Wang, Xue Qi; Delaidelli, Alberto; Rafn, Bo; Cran, Jordan; Zhang, Fan; Zhang, Haifeng; et al.
Abstract: Outcomes for metastatic Ewing sarcoma and osteosarcoma are dismal and have not changed for decades. Oxidative stress attenuates melanoma metastasis, and melanoma cells must reduce oxidative stress to metastasize. We explored this in sarcomas by screening for oxidative stress sensitizers, which identified the class I HDAC inhibitor MS‐275 as enhancing vulnerability to reactive oxygen species (ROS) in sarcoma cells. Mechanistically, MS‐275 inhibits YB‐1 deacetylation, decreasing its binding to 5′‐UTRs of NFE2L2 encoding the antioxidant factor NRF2, thereby reducing NFE2L2 translation and synthesis of NRF2 to increase cellular ROS. By global acetylomics, MS‐275 promotes rapid acetylation of the YB‐1 RNA‐binding protein at lysine‐81, blocking binding and translational activation of NFE2L2, as well as known YB‐1 mRNA targets, HIF1A, and the stress granule nucleator, G3BP1 . MS‐275 dramatically reduces sarcoma metastasis in vivo, but an MS‐275‐resistant YB‐1K81‐to‐alanine mutant restores metastatic capacity and NRF2, HIF1α, and G3BP1 synthesis in MS‐275‐treated mice. These studies describe a novel function for MS‐275 through enhanced YB‐1 acetylation, thus inhibiting YB‐1 translational control of key cytoprotective factors and its pro‐metastatic activity. Synopsis: Class 1 HDAC inhibitors including MS‐275 inhibit the RNA binding protein YB‐1 by enhancing its acetylation. This reduces its affinity to mRNA targets under cellular stress, and decreases tumor cell fitness and metastatic capacity. YB‐1 translationally activates NRF2 synthesis under oxidative stress. MS‐275‐mediated YB‐1 acetylation reduces translation of multiple YB‐1 translational targets. MS‐275 blocks metastasis of childhood sarcoma cell lines and PDX tumors in pre‐clinical models. Abstract : Class 1 HDAC inhibitors including MS‐275 inhibit the RNA binding protein YB‐1 by enhancing its acetylation. This reduces its affinity to mRNA targets under cellular stress, and decreases tumor cell fitness and metastatic capacity.